Peningkatan Kinerja Simpang 3 Jalan Antisipasi Aktivitas SPBU dan U-Turn - Pratama, Mario Wahyu; Idham, Muhammad (Lembaga Teewan Journal Solutions, 2026)
Vehicle movements entering and exiting fuel stations (SPBU) and U-turn maneuvers can reduce intersection performance by increasing traffic conflicts and decreasing the effective width of the approach. This study evaluates the Perwira Three-Legged Intersection performance under existing conditions, five-year and ten-year projections, analyzes SPBU and U-turn influences, and assesses improvement alternatives based on PKJI 2023. Field surveys collected geometric, traffic volume, roadside friction, SPBU, and U-turn data. Analysis used capacity, degree of saturation (Dj), delay, level of service, and queue length. Results show Dj increased from 0.84 to 0.91 and 1.00 under five-year and ten-year projections, with average delay rising from 97 s/pcu to 110 s/pcu and 117 s/pcu. SPBU activities were the dominant factor, reducing effective approach width by 0.7 m, while U-turn impact was minor. The proposed widening improved performance, reducing Dj to 0.68–0.81 and delay to 59–74 s/pcu, thus improving level of service and accommodating future traffic growth.